Different wave structures and stability analysis for the generalized (2+1)-dimensional Camassa-Holm-Kadomtsev-Petviashvili equation - Osman, M. S.; İnç, Mustafa; Liu, Jian-Guo; Hossein, Kamyar; Yusuf, Abdullahi (Iop Publishing Ltd, 2020)
The main concern of the present article is to study the generalized (2+1)-dimensional Camassa-Holm-Kadomtsev-Petviashvili equation describing the dispersion role in the formation of patterns in liquid drops. To this end, a series of different wave structures including lump wave solutions, one-soliton, double-soliton, and triple-soliton solutions are formally retrieved through the ansatz (positive quadratic and exponential functions) technique. Furthermore, the stability analysis for the governing model is explored in a systematic manner.
Keywords: 2D-gCHKP equation; ansatz technique; lump wave solutions; multi-soliton solutions; stability analysis